Antiproliferative and apoptotic effects of telmisartan in human glioma cells - Yung-Lung Chang; Chung-Hsing Chou; Yao-Feng Li; Li-Chun Huang; Ying Kao; Dueng-Yuan Hueng; Chia-Kuang Tsai (Cancer Cell International, 2023)
Abstract Glioblastoma is the most common primary central nervous system tumor in adults. Angiotensin II receptor blockers (ARBs) are broadly applied to treat hypertension. Moreover, research has revealed that ARBs have the capacity to suppress the growth of several cancer types. In this study, we assessed the effects of three ARBs with the ability to cross the blood brain barrier (telmisartan, valsartan and fimasartan) on cell proliferation in three glioblastoma multiforme (GBM) cell lines. Telmisartan markedly suppressed the proliferation, migration, and invasion of these three GBM cell lines. Microarray data analysis revealed that telmisartan regulates DNA replication, mismatch repair, and the cell cycle pathway in GBM cells. Furthermore, telmisartan induced G0/G1 phase arrest and apoptosis. The bioinformatic analysis and western blotting results provide evidence that SOX9 is a downstream target of telmisartan. Telmisartan also suppressed tumor growth in vivo in an orthotopic transplant mouse model. Therefore, telmisartan is a potential treatment for human GBM.